Experimental Modal Analysis Assessment of a Scaled-Down Tower Crane Mast to be Used in Experimental Studies - Kenan, Hamit; Azeloglu, C. Oktay (SPRINGER, 2023)
Testing of large and heavy structures or systems in real-size form is not a preferred method because of expectations from experimental studies, such as repeatability, less time consumption, less cost, and realistic environmental conditions. Thus, it is more reasonable to design a scaled model that represents a real-size structure and to perform experimental studies with this model. In this research, a tower crane mast that is the dominant part for oscillation of the whole crane system and so large for the laboratory environment is considered and aimed to obtain a scaled physical model that dynamically represents the real structure in order to experimentally investigate the dynamic response of a tower crane under the seismic effect. In this context, a tower crane mast model was manufactured as 1/30 scaled size and an experimental modal analysis test was performed on the physical model. The competency of the scaled model to represent the real-size model was presented by theoretical and experimental studies. Results of these studies show that the scaled model represents the dynamics of the real-size system effectively.
Keywords: Tower crane; Scaled model; Similitude theory; Experimental modal analysis; Engineering